2019
DOI: 10.1242/jcs.228338
|View full text |Cite
|
Sign up to set email alerts
|

Cytocortex-dependent dynamics of Drosophila Crumbs controls junctional stability and tension during germ band retraction

Abstract: During morphogenesis, epithelia undergo dynamic rearrangements, which requires continuous remodelling of junctions and cell shape, but at the same time mechanisms preserving cell polarity and tissue integrity. Apico-basal polarity is key for the localisation of the machinery that enables cell shape changes. The evolutionarily conserved Drosophila Crumbs protein is critical for maintaining apico-basal polarity and epithelial integrity. How Crumbs is maintained in a dynamically developing embryo remains largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 107 publications
2
6
1
Order By: Relevance
“…For instance, E-cad could be internalized at a faster rate in the absence of the Crb complex in epi-NSCs. This working hypothesis is consistent with the notion that the Crb complex stabilizes AJs and regulates MyoII at junctions to maintain epithelium integrity during morphogenesis (Harris and Tepass, 2008;Flores-Benitez and Knust, 2015;Campbell et al, 2009;Bajur et al, 2019;Perez-Mockus et al, 2017b;Röper, 2012;Salis et al, 2017;Sen et al, 2012). It is also consistent with our observation that loss of Crb regulation by Neur led to E-cad persisting in NSCs past the TZ.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, E-cad could be internalized at a faster rate in the absence of the Crb complex in epi-NSCs. This working hypothesis is consistent with the notion that the Crb complex stabilizes AJs and regulates MyoII at junctions to maintain epithelium integrity during morphogenesis (Harris and Tepass, 2008;Flores-Benitez and Knust, 2015;Campbell et al, 2009;Bajur et al, 2019;Perez-Mockus et al, 2017b;Röper, 2012;Salis et al, 2017;Sen et al, 2012). It is also consistent with our observation that loss of Crb regulation by Neur led to E-cad persisting in NSCs past the TZ.…”
Section: Discussionsupporting
confidence: 92%
“…Sdt interacts with Pals1-associated tight junction (Patj) to form a Crb-Sdt-Patj complex (Bulgakova and Knust, 2009). The apical Crb complex is required to stabilize adherens junctions (AJs) and maintain epithelial integrity during tissue remodeling in Drosophila (Harris and Tepass, 2008;Bajur et al, 2019;Flores-Benitez and Knust, 2015;Campbell et al, 2009;Perez-Mockus et al, 2017b;Röper, 2012;Salis et al, 2017). Recently, the conserved E3 ubiquitin ligase Neuralized (Neur) was found to interact with specific isoforms of Sdt, and this interaction appeared to target the Crb complex proteins for endocytosis and degradation (Chanet and Schweisguth, 2012;Perez-Mockus et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by using dominant active or inactive forms of Rab5 (Zhang et al, 2007), we obtained inconsistent results (data not shown), probably due to pleiotropic effects of these versions of Rab5, which tend to titer effectors shared with other Rab proteins (Pylypenko et al, 2017; Müller and Goody, 2018). Although loss of β H -Spec function has been linked to increased endocytosis in some Drosophila epithelia (Williams et al, 2004; Pellikka et al, 2002; Richard et al, 2009; Phillips and Thomas, 2006), or Crb mobility in the embryonic epidermis (Bajur et al, 2019) data presented here support the conclusion that in larval SGs Crb predominantly regulates apical membrane traffic and secretion, though we cannot completely rule out a minor contribution of endocytosis to the phenotypes observed.…”
Section: Discussioncontrasting
confidence: 61%
“…While it is not known whether the kinetics of E-cad endocytosis vary between NE and epi-NSCs, we note that this view is entirely consistent with the notion that Crb stabilizes AJs and is required to maintain epithelium integrity in contexts of morphogenesis, e.g. cell delamination, cell-cell intercalation and division (Harris and Tepass, 2008;Bajur et al, 2019;Flores-Benitez and Knust, 2015;Campbell et al, 2009;Perez-Mockus et al, 2017b;Röper, 2012;Salis et al, 2017). Future studies will address whether Neur promotes a faster turn-over of E-cad via its regulatory activity on the Crb complex and/or cortical actomyosin.…”
Section: Discussionsupporting
confidence: 84%
“…These NSCs give rise to the medulla neurons that will comprise part of the visual processing center of the adult brain. This proneural wave is proposed to travel through the NE via an required to stabilize AJs and maintain epithelial integrity during tissue remodeling in Drosophila (Harris and Tepass, 2008;Bajur et al, 2019;Flores-Benitez and Knust, 2015;Campbell et al, 2009;Perez-Mockus et al, 2017b;Röper, 2012;Salis et al, 2017). Recently, the conserved E3 ubiquitin ligase Neuralized (Neur) was found to directly interact with specific isoforms of Sdt and this interaction appeared to target Crb for endocytosis and degradation (Perez-Mockus et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%